2011
DOI: 10.1002/eji.201041040
|View full text |Cite
|
Sign up to set email alerts
|

PA28 and the proteasome immunosubunits play a central and independent role in the production of MHC class I‐binding peptides in vivo

Abstract: Summary Proteasomes play a fundamental role in the processing of intracellular antigens into peptides that bind to MHC class I molecules for presentation to CD8 T cells. Three IFNγ-inducible catalytic proteasome (immuno)subunits as well as the IFNγ-inducible proteasome activator PA28 dramatically accelerate the generation of a subset of MHC class I-presented antigenic peptides. To determine whether these IFNγ-inducible proteasome components play a compounded role in antigen processing, we generated mice lackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 48 publications
(95 reference statements)
1
56
0
2
Order By: Relevance
“…The data are compelling, and several reports point to i-proteasome deficiency leading to the lack of suitable peptides for class I occupancy. 47,69 The correlation between MECL-1 and LMP7 deficiency and reduced surface expression of MHC class I is based on two observations: that expression of MHC class I is dependent on occupancy of the cleft in the MHC α chain, 70,71 and that chymotrypsin-like activity of the immune subunit provides a larger pool of precursors. While these hypotheses are sound, direct evidence for a shortage of i-proteasome-generated peptides being the rate-limiting step for maturation of MHC class I molecules and their expression on the cell surface is lacking, as total proteasome content is relatively constant, and standard proteasome would continue to provide peptide precursors, even if the repertoire was altered.…”
Section: Immunoproteasome Functionmentioning
confidence: 99%
“…The data are compelling, and several reports point to i-proteasome deficiency leading to the lack of suitable peptides for class I occupancy. 47,69 The correlation between MECL-1 and LMP7 deficiency and reduced surface expression of MHC class I is based on two observations: that expression of MHC class I is dependent on occupancy of the cleft in the MHC α chain, 70,71 and that chymotrypsin-like activity of the immune subunit provides a larger pool of precursors. While these hypotheses are sound, direct evidence for a shortage of i-proteasome-generated peptides being the rate-limiting step for maturation of MHC class I molecules and their expression on the cell surface is lacking, as total proteasome content is relatively constant, and standard proteasome would continue to provide peptide precursors, even if the repertoire was altered.…”
Section: Immunoproteasome Functionmentioning
confidence: 99%
“…Several studies revealed that proteasomal activators are affecting substrate entry/exit (channeling) [5,6] as well as proteasomal cleavage site preferences. Coincidentally, hetero-heptameric PA28ab complexes and immunoproteasome isoforms differentially affect proteasomal processing and presentation of certain major histocompatibility complex (MHC) class-I epitopes [7].…”
Section: Introductionmentioning
confidence: 99%
“…The binding of PSME1 and PSME2 to the i20S has recently been shown to increase the capacity of i-proteasomes to selectively degrade oxidized proteins (44) and accelerate the generation of a subset of MHC class I-presented antigenic peptides (9,45,46). In addition, in situ PLA showed that both PSME1 associated proteasomes and i-proteasomes were mainly localized in the cytosol of C2C12 cells.…”
Section: Discussionmentioning
confidence: 99%